O IMPACTO DA ESPIRITUALIDADE NO TRABALHO E DE PERCEPÇÃO DE SAÚDE ORGANIZACIONAL SOBRE COMPORTAMENTOS DE CIDADANIA ORGANIZACIONAL - Garcia, Fabiana Aparecida Silva (2013)
Increasingly, the human factor is evidenced at the competitive and globalized market. So, constantly, companies are concerned with the quality of work, for its employees can feel happy about their achievement, not being affected by the pressures of daily life. In this context, this dissertation aimed at analyzing the relationship between workplace spirituality, perception of organizational health and organizational citizenship behaviors among university teachers. In the study are included 82 workers from both genders, aged between 28 and 63 years old, working in the state of São Paulo in public and private Universities. As a tool for collecting data was used a self-filling composed of three scales that measured the variables of the research. So, this study also aimed to present, interpret and discuss the relationships between variables, but also to test hypotheses regarding the proposed conceptual model through a survey using a quantitative approach, where the collected data were analyzed by applying parametric statistical methods (calculation of descriptive statistics: means, standard deviations, precision index of measures, t test and correlations, multivariate statistical calculations: standard multiple linear regression). The data analysis was performed using the statistical software Statistical Package for the Social Science SPSS, version19.0 for Windows. The results showed that among the three dimensions of organizational citizenship behaviors, only two image promoting of the organization and cooperation with colleagues received positive impact of perceptions of organizational health and workplace spirituality. For these two classes of shares organizational citizenship became more evident when the power impact of the work. The study allowed us to conclude that the actions of creative suggestions made by employees, have no influence on how much they believe that the company has a satisfactory health and how much they experience or not the spirituality in the organizational environment.